Analisis Penerapan Akuntansi Pertanggungjawaban Dengan Anggaran Sebagai Alat Pengendalian Biaya (Studi Kasus Pada Kantor Desa Bloro Kecamatan Nita) - Nega, Yelita; Dince , Maria Nona; Yuneti, Katharina (Jurnal CUAN Universitas Nusa Nipa Maumere, 2025)
This research aimed to determine the extent of acountability accounting implementation at the Bloro Village office, Nita Sub-district. This research used a qualitative approach, utilizing methodes of interviews, documentation, and observation to examine the requirements for implementing accounting with budgeting as a cost control tool carried out in Bloro Village, Nita Sub-distric, which involved the village head and financial treasuurer. the results obatined in this researrch showed that Bloro Village has not fully implemented accountability accounting because the process of preparing the budget did not involve all village officials, the prepations was stil based on estimates, and there was no clear spearation between controllable and unccontrollable costs. cost contol was alos quite efficient, even though there was still a difference between the budgeted cost and the actual costs.